ETUDE EXPERIMENTALE DE L'HEMIATROPHIE FACIALE PROGRESSIVE: EFFETS DE LA SYMPATHECTOMIE CERVICALE CHEZ L'ANIMAL - Resende, L. A.L.; Dal Pai, V.; Alves, A. (My University, 1991)
Progressive facial hemiatrophy (Romberg's syndrome) is of unknown cause and uncertain pathogenesis. The main pathogenetic hypotheses are : sympathetic system alterations, localized scleroderma, trigeminal changes, possibly of genetic origin. To test the hypothesis of sympathetic system alterations, we designed an experimental model with ablation of the superior cervical sympathetic ganglion in rabbits, cats and dogs. All the animals were operated upon when 30 days old and were examined monthly for 1 year. During this period localized alopecia, corneal ulceration, keratitis, strabismus, enophthalmos, ocular atrophy, hemifacial atrophy and slight bone atrophy on the side of the sympathectomy were observed. Thus, cervical sympathectomy reproduces in animals the principal clinical alterations of Romberg's syndrome. Our data suggest that the sympathetic system is involved in the pathogenesis of this syndrome.
Experimental study of progressive facial hematrophy: Effects of cervical sympathecty in animals